Hadith #2866 - Sunan Abi Dawud - Abdah bin 'Abdullah al-Saffar عبدة بن عبد الله الصفار; Abdul Samad bin 'Abdul Warith bin Sa'id عبد الصمد بن عبد الوارث بن سعيد; Abu Hurairah; Nasr bin 'Ali bin Nasr bin 'Ali; Shar bin Hushab al-Asha'ri شهر بن حوشب الأشعري (Sunan Abi Dawud)
The Prophet (ﷺ) said: A man giving a dirham as sadaqah (charity) during his life is better than giving one hundred dirhams as sadaqah (charity) at the moment of his death.
Grade: Da'if

Hadith #4433 - Sunan Abi Dawud - Abdah bin 'Abdullah al-Saffar عبدة بن عبد الله الصفار; Abdah bin Sulaiman al-Klabi عبدة بن سليمان الكلابي أبو محمد الكوفي; Abdul 'Aziz bin 'Umar bin 'Abdul-'Aziz عبد العزيز بن عمر بن عبد العزيز; Harmy bin Hafs bin 'Umar حرمي بن حفص; Khalid bin al-Lajlaj al-Amiri خالد بن اللجلاج العامري; Muhammad bin 'Abdullah bin 'Alatha محمد بن عبد الله بن علاثة (Sunan Abi Dawud)
The Prophet (ﷺ) smelt the breath of Ma’iz.
Grade: Sahih